Ο βυζαντινός λόγιος και ο αναγεννησιακός αστρονόμος: Η μετάφραση των "Ἐπιστολῶν" του Θεοφύλακτου Σιμοκάττη από τον Νικόλαο Κοπέρνικο - ΜΕΡΙΑΝΟΣ Γεράσιμος; ΣΑΚΟΡΡΑΦΟΥ Κυριακούλα (Byzantina Symmeikta, 2009)
THE BYZANTINE SCHOLAR AND THE RENAISSANCE ASTRONOMER: THE TRANSLATION OF THEOPHYLAKTOS SIMOKATTES’ LETTERS BY NICOLAUS COPERNICUS The Latin translation of the Byzantine writer Theophylaktos Simocattes’ Letters (Ἐπιστολαὶ ἠθικαί, ἀγροικικαί, ἑταιρικαί) by the astronomer Nicolaus Copernicus in 1509 is a work that has been neglected. This translation was Copernicus’ first publication, thirty four years before his celebrated De revolutionibus orbium coelestium was published (1543). In this paper, our aim is to discuss the reasons that led Copernicus to the translation of this particular Greek literary work. We argue that his choice was pertinent on one hand to his astronomical interests and his need to learn Greek, and on the other hand to his intention to participate in the emerging Humanist movement in early sixteenth-century Poland.